Direitos humanos e empresas: uma análise dos parâmetros brasileiros de responsabilidade por danos à mão de obra terceirizada no setor de confecção de vestuário - Matos, Laura Germano (2019)
This paper aims to investigate the civil liability guidelines used by Brazilian Labor Courts to condemn clothing factory companies for violations occurred on their suply chains. The damages that affect outsourced workers are considered violations to human rights, because they involve the use of slave labor, degrading conditions and other circumstances of exploitation that affect the minimum level of protection of consolidated human rights. It is verified that companies in the clothing industry, for acting through long and branched chains of suply, subcontracting workshops to deal with the labor force, claim they are not liable for the situations of breach of rights in which workers are caught, but on the other hand, they are frequently condemned to financial reparation. In this sense, this research compares the Brazilian legal apparatus on the theme with the arguments that are actually used in some emblematic cases by labor courts to condemn companies, discussing who in fact should be responsable for these problems. The cases analysed involved Zara, M. Officer, Pernambucanas and Serafina-Collins. Through this comparative analysis, this study maps the most used arguments in the decisions, trying to elucidate and systematize an eventual pattern of corporate accountability. The methodology is qualitative with a descriptive, exploratory and propositive approach, through a bibliography review and analysis of the criteria adopted by courts to atribute liability and demand repair in practical cases. It was concluded that the adopted criteria lead to an interpretation of the corporations according to their sphere of influence, towards increasing their level of binding with their suply chains and therefore their duties of protection of the workers involved.